Effect of Pelvic Tilt on Synchronisation and Stability of Riders in Sitting Trot. (June 2014) - Pettit, I; Walker, V; Tranquille, C; Spear, J; Murray, R
Abstract : Introduction: Rider movement may influence horse‐rider interaction, yet little is known about what physical attributes affect postural stability. This study aimed to compare pelvic control and postural stability of riders on the floor and whilst riding. Methods: 33 riders were assessed by a physiotherapist and subjectively graded according to ability to tilt the pelvis in isolation: 1 = poor, 2 = better plus compensations, which were either A = lumbar spine inclusion B = full body lean, 3 = good. Riders wore markers on (1) greater trochanter of the femur, (2) iliac crest, (3) greater tubercle of the humerus. A marker was placed over the horse's tuber sacrale (4). Two‐dimensional high‐speed motion‐capture (240 Hz) recorded four strides of collected sitting trot in a straight line from the left side. Distance between markers was measured at midstance, maximum hindlimb protraction and retraction. Synchronisation was determined by the difference in time (secs) between the tuber sacrale of the horse and pelvis of the rider at these stride points. One‐way ANOVA was used to compare synchronisation between groups. Student's independent t‐test was used to compare marker distance. Results: For pelvic tilt, no grade 3 riders were seen. Grade 2 riders were more synchronised with the horse during left hind diagonal suspension phase (P = 0.011) and had smaller horizontal distances between markers 1–2, 2–3 and 1–3 respectively at all points of the stride (midstance: P<0.042; hindlimb protraction: P<0.049; hindlimb retraction: P<0.013). Comparing compensation types, grade A riders were better synchronised with the horse at midstance phase (P = 0.014). Conclusions: Results suggest that control of pelvic movement may have an impact on horse‐rider synchronisation. Ethical Animal Research: This project was approved by the Animal Health Trust Clinical Research Ethics Committee. Explicit owner informed consent for participation in this study is not stated.Sources of funding:  The Elise Pilkington Charitable Trust, British Dressage and Dr. Bechtolsheimer.Competing interests:  none.